KONFLIK PEMBANGUNAN RUMAH IBADAH DI DESA PUNTI KAYU KECAMATAN BATANG PRANAP KABUPATEN INDRAGIRIHULU - Firdaus "; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study is to determine the cause of the conflict in the construction of houses of worship in the backwoods seranggeh pabrik and the impact caused by the conflict and what kind of settlement efforts that have been done.This research uses qualitative research methods by taking some people as respondents who are trusted to represent from all respondents.To collect data from the respondents used direct observation methods, interviews and documentation.This study sees that people always have a variety of needs so that conflicts often occur between communities and conflicts also occur because of differences of opinion and goals between interest groups and pseudo-groups, this is happening in backwoods seranggeh pabrik, where social conflict in the construction of houses of worship has not been resolved entirely because there are still differences of opinion, interests and rejection of the hamlet community seranggeh pabrik.In the settlement of this conflict has been taken by way of negotiation and mediation but not also get an agreement between the two conflicting groups, so the problem is solved by means of abitration that is the absolute decision of the village chief who deliberate with the regent of Indragiri hulu to resolve the conflict that must be obeyed by both parties in conflict.Keywords: Social Conflict, Development of House of Worship